ANALYSIS OF PRETREATMENT AND POST TREATMENT PAIN USING VISUAL ANALOG SCALE IN TEMPOROMANDIBULAR JOINT DISORDERS - G, Indra.; G., Maragathavalli; Rajendran, Deepika (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Temporomandibular joint disorder (TMD) is one of the most common and painful disorders. Numerous factors aid the reason for TMD in individuals. The Visual Analog Scale (VAS) is a measuring unit used to measure the intensity of the pain. VAS helps to quantify the patient's pain and can be used for any orofacial pain disorder. The study aims to evaluate the pre-treatment and post-treatment pain in patients present with TMD with VAS.MATERIALS AND METHODS: A total of 70 patients were taken in the study, and their pain was studied prior and post-treatment using VAS to quantify the intensity of the pain experienced by them. The study period was between July 2019 and March 2020.Results: Study results showed that the usage of VAS in understanding the intensity of pain was beneficial. Comparing the pre- and post-treatment pain scores between the male and female populations, the female participants were able to accurately explain the difference in the intensity of the pain compared to their counterparts.Conclusion: Evaluating the intensity of pain experienced by an individual may help in altering the treatment modalities and can account for a better quality of life (QoL).